Where have all the bees gone? - Hirsch, Rebecca E. (Twenty-First Century Books, 2020)
Informs readers about different bee species and the global extinction threats they face from disease, pesticides, climate change, and loss of habitat. Discusses the role bees play in the life cycle of some of the products we consume--fruits, vegetables, and nuts--and examines how people can help. Includes color images, source notes, a bibliography, and sources for further learning.